2018
DOI: 10.2478/auom-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Type I + Helicoidal Surfaces with Prescribed Weighted Mean or Gaussian Curvature in Minkowski Space with Density

Abstract: In this paper, we construct a helicoidal surface of type I+ with prescribed weighted mean curvature and Gaussian curvature in the Minkowski 3−space ${\Bbb R}_1^3$with a positive density function. We get a result for minimal case. Also, we give examples of a helicoidal surface with weighted mean curvature and Gaussian curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Also, some types of surfaces have been studied by geometers in other spaces such as Minkowski 3-space and Galilean 3-space with density. For instance, a helicoidal surface of type + with prescribed weighted mean curvature and Gaussian curvature in Minkowski 3-space and weighted minimal translation surfaces in Minkowski 3-space with density have been constructed in [25] and [30], respectively. In [31], weighted minimal translation surfaces in the Galilean 3-space with log-linear density have been classified and in [19], weighted minimal and weighted flat surfaces of revolution in Galilean 3-space with density 2 + 2 + 2 have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some types of surfaces have been studied by geometers in other spaces such as Minkowski 3-space and Galilean 3-space with density. For instance, a helicoidal surface of type + with prescribed weighted mean curvature and Gaussian curvature in Minkowski 3-space and weighted minimal translation surfaces in Minkowski 3-space with density have been constructed in [25] and [30], respectively. In [31], weighted minimal translation surfaces in the Galilean 3-space with log-linear density have been classified and in [19], weighted minimal and weighted flat surfaces of revolution in Galilean 3-space with density 2 + 2 + 2 have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…where ε B = B, B L = ±1 and ε T = T, T L = ±1, [5]. Some studies which are studied in the Minkowski 3-dimensional space can be found in [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A hypersurface is called weighted flat (or -flat), if its weighted Gaussian curvature vanishes. After these definitions, lots of studies have been done by differential geometers about weighted manifolds, for instance [16][17][18][19][20][21][22][23][24][25]. Let we take ( ) = (ℎ ) × ( ) −1 .…”
Section: Introductionmentioning
confidence: 99%